2020
DOI: 10.1002/tax.12314
|View full text |Cite
|
Sign up to set email alerts
|

Generic boundaries in subtribe Saussureinae (Compositae: Cardueae): Insights from Hyb‐Seq data

Abstract: The subtribe Saussureinae is a highly speciose group with more than 600 species distributed in the Northern Hemisphere and is particularly species‐rich at the high mountains of central and eastern Asia. Saussurea and Jurinea are the two main genera described within the subtribe. However, up to 15 satellite genera are recognized in some recent taxonomic treatments with an analytical viewpoint. For the first time, we carried out a complete sampling to clarify generic boundaries based on a well‐resolved phylogeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…(now known as subtribe Saussureinae). However, recent molecular work (Herrando-Moraira et al, 2020) has clearly shown that this species lies in the Dolomiaea clade. Also, detailed morphological investigation shows that it should belong to Dolomiaea rather than Jurinea due to the absence of scales on the receptacle and yellowish pappus bristles that are not inserted on a conic cupule in Dolomiaea as compared to the presence of short scales on the receptacle and white pappus bristles that are inserted on a conic cupule in Jurinea.…”
Section: Conservation Statusmentioning
confidence: 91%
See 3 more Smart Citations
“…(now known as subtribe Saussureinae). However, recent molecular work (Herrando-Moraira et al, 2020) has clearly shown that this species lies in the Dolomiaea clade. Also, detailed morphological investigation shows that it should belong to Dolomiaea rather than Jurinea due to the absence of scales on the receptacle and yellowish pappus bristles that are not inserted on a conic cupule in Dolomiaea as compared to the presence of short scales on the receptacle and white pappus bristles that are inserted on a conic cupule in Jurinea.…”
Section: Conservation Statusmentioning
confidence: 91%
“…Therefore, Dolomiaea has been of great interest for systematists and has remained an integral part of the Saussurea -Jurinea group. However, recent studies have shown that Dolomiaea is a distinct genus and has been recovered as a well-supported 2 A taxonomic revision of Dolomiaea in India clade in molecular analyses (Wang et al, 2007;Herrando-Moraira et al, 2020;Kasana et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on morphological evidence and phylogenetic analysis using Hyb-Seq data, generic delimitation in the subtribe Saussureinae was recently proposed for the three main clades, Dolomiaea DC., Saussurea, and Jurinea (Herrando-Moraira, 2020). As a result, all species of Himalaiella have been moved to Jurinea, which now consists of over 200 species, including unarmed dwarf shrubs, shrublets, and perennial herbs in Eurasia (Herrando-Moraira et al, 2020). Consequently, three species in Myanmar belong to Jurinea: J. deltoidea (DC.)…”
mentioning
confidence: 99%